New Zealand : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1997)
This Selected Issues paper and Statistical Appendix reviews the performance of New Zealand and compares its growth rates of output, inputs, and total factor productivity during 1978-96 with 10 other economies. This study applies a common methodology across countries, not only for the growth accounting exercise itself, but also to derive the key variables used in the exercise. National data sources are used only for the most basic data. The paper also reviews New Zealand's experience with inflation targeting.